CUSTOMER RELATIONSHIP MANAGEMENT ASSESMENT AND CUSTOMER RELATIONSHIP MARKETING TO IMPROVE INPATIENT UTILISATION - Wahyuningsih, Aries (Jurnal Penelitian STIKES Kediri, 2013)
Customer Relationship Management supports a company in providing service to customers in real time and builds a relationship with each customer through the usage of customer’s information. Customer Relationship Marketing is a process to manage detailed information about individual customers and all customer points in order to manage the detailed information of each customer. The design of this study was observational by conducting market research. The respondents were 60 patients and 15 employees of Obstetrics and Gynecology Ward. Study of Customer Relationship Management and Customer Relationship Marketing was conducted after result of market research obtained. The result of this study showed that most of respondents had less knowledge about Kediri Baptist Hospital’s promotion and perception about the expensive cost, they also felt dissatisfaction towards the waiting room facilities and the administrative procedures. The result were discussed in FGD with hospital’s management and then decide the recommendations. Those included several things such as: improving human resources competence, one day care labor service, customer gathering, improving 24 hours nurse line post services.